An Examination of Psychometric Characteristics and Factor Structure of Death Anxiety Scale Within a Sample of Iranian Patients With Heart Disease - Mohammad Ali Soleimani; Saeed Pahlevan Sharifi; Ameneh Yaghoobzadeh; Kelly-Ann Allen; Hamid Sharif Nia (Shahrekord University of Medical Sciences, 2017)
Background and aims: Despite a substantial body of work examining the role of death anxiety (DA) in an individual's quality of life, there is a lack of valid and standardized instruments that could measure this construct for patients with coronary heart disease (CHD). The objective of this study was to examine the psychometric characteristics and factor structure of the Templer Death Anxiety Scale (TDAS) within a sample of Iranian patients who had experienced acute myocardial infarction (AMI). Methods: In this study, 584 patients with CHD completed the TDAS. A principal components analysis evaluated dimensionality of the measuring instrument. Reliability and validity were assessed. Results: Factor analysis found 3 distinct factors (fear of death due to illness, fear of facing death, and distress due to short time of life). Convergent and discriminant validity for the constructs of the TDAS were fulfilled. The internal consistency for the measure was < 0.70. Conclusion: Findings revealed that the Persian version of the TDAS is a valid and reliable instrument that can be used for the assessment and evaluation of DA in Iranian patients with CHD.